Registration of Purified Accessions for the U.S. Peanut Mini‐Core Germplasm Collection. Issue 1 (27th September 2013) - Chen, Charles Y.; Barkley, Noelle A.; Wang, Ming L.; Holbrook, C. Corley; Dang, Phat M.
Abstract : Many accessions of the USDA peanut ( Arachis hypogaea L.) germplasm collection are heterogeneous. Advances in genomics technology have highlighted the need for collections of homogeneous accessions. The objectives of this research were to purify accessions of the USDA mini‐core collection and to characterize this collection for morphological traits. Twenty seeds of 104 accessions (Reg. No. GP‐131 to GP‐234) of the peanut mini‐core collection were planted at Dawson, GA, in 2008 under irrigated conditions. The seeds from five phenotypical uniform plants were harvested, bulked, and planted in Headland, AL, in 2009 to continue the purification process. In 2010, homogenous seeds of each accession were planted in Headland, AL, to increase seed counts for chemical analysis and genotyping. In addition to morphological characters and seed chemical composition, the accessions were evaluated for spotted wilt resistance caused by a Tomato spotted wilt virus (TSWV) and early leaf spot resistance caused by Cercospora arachidicola (Hori), which is a major disease that significantly affects peanut production in the southeast. The morphological and chemical data, along with images of pod and seed traits, were entered in the Germplasm Resources Information Network (GRIN); detailed information can be found at http://www.ars‐grin.gov/cgi‐bin/npgs/html/csr.pl?PEANUT . The results showed that after purification, these accessions not only preserved similar genetic variation in the collection but also became more homogeneous compared to the original accessions. A small number of seed of the purified accession can be obtained for research and breeding purposes through the National Plant Germplasm System (http://www.ars‐grin.gov/npgs/orders.html ).